Purification and characterization of a lectin of the swartzieae legume taxa - Fernandes, Andréia Varmes; Ramos, Márcio Viana; Vasconcelos, Ilka Maria Aria; Monteiro, Cristina A.; Moreno, Frederico Bruno Mendes Batista; Pereira, José Odair; Gonçalves, José Francisco de Carvalho (Protein and Peptide Letters, 2012)
This work aimed at describing the first biochemical and structural data of a lectin belonging to Swartzieae, a primitive Legume Taxa. A lactose-binding seed lectin (SLL) was purified by affinity chromatography of crude saline extracts of Swartzia laevicarpa on immobilized lactose. The SLL agglutinated rabbit erythrocytes but not rat or human (A, B, O) erythrocytes. Lectin activity was retained after heating at 100 °C for 15 min and was best inhibited by Nacetylgalactosamine, lactose and galactose. The lectin exhibited a single electrophoretic pattern that corresponded to a molecular mass of 29,000 Da, which was confirmed by MS analysis. In addition, the lectin reacted positively with Schiff's reagent. The unique N-terminal amino acid sequence (39 residues) and the internal peptide sequence were determined by Edman degradation and MS/MS, respectively. The sequencing revealed complete homology of the SLL with legume lectins belonging to primitive groups (Dalbergieae and Sophoreae). The SLL (at 1 mg/ml) did not exhibit antifungal activity against various phytopathogens or cytotoxicity (at 100 μg/ml) towards different cancer cell lines. © 2012 Bentham Science Publishers.
Keywords: Galactose; Lactose; Lactose Binding Seed Lectin; N Acetylgalactosamine; Plant Extract; Plant Lectin; Sodium Chloride; Swartzia Laevicarpa Extract; Unclassified Drug; Chromatography, Affinity; Amino Acid Sequence; Amino Terminal Sequence; Animals Cell; Anti-fungal Activity; Bacterium Isolate; Cancer Cell Culture; Chemical Analysis; Chemical Reaction; Colon Cancer; Concentration Response; Controlled Study; Dalbergia; Drug Cytotoxicity; Enzyme Inhibition; Erythrocyte; Fusarium Solani; Glioblastoma; Glomerella Lindemuthiana; Hemagglutination; Ic 50; In Vitro Study; Legume; Mass Spectrometry; Molecular Weight; Nonhuman; Ovary Cancer; Seed Plant; Protein Analysis; Protein Degradation; Protein Function; Protein Purification; Protein Structure; Rabbit; Sequence Homology; Sophora; Structure Analysis; Swartzia Laevicarpa; Temperature Sensitivity; Thanatephorus Cucumeris; Toxicity Testing; Acetylgalactosamine; Amino Acid Sequence; Animal; Cell Death; Chromatography, Affinity; Electrophoresis; Fabaceae; Fungi; Galactose; Hemagglutination; Hemagglutination Tests; Humans; Lactose; Molecular Sequence Data; Molecular Weight; Neoplasms; Peptide Fragments; Plant Lectins; Rabbits; Rats; Seeds; Spectrometry, Mass, Matrix-assisted Laser Desorption-ionization; Tumor Cells, Cultured